The dispute over the title “ecumenical” between the bishops of Rome and Constantinople at the end of the 6th century - Aleksei Migalnikov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Abstract: The article analyzes the epistles of Pope Gregory the Great (590-604), directed against the title “ecumenical” (οiκουμενικός) of the patriarchs of Constantinople. It is shown that the pope opposed the title throughout his pontificate, although the nature of this confrontation changed depending on various circumstances, up to the temporary cessation of direct polemics. The latter fact forces some researchers to assume a qualitative change in the attitude of Pope Gregory to the title. However, the analysis of sources shows the opposite: not receiving sufficient support from the emperor Maurice and the Eastern patriarchs Eulogius of Alexandria and Anastasius I of Antioch, while not wanting to cause a church schism and, as a result, reducing the intensity of the dispute, the pope at the same time maintained a negative opinion about the title and more than once used the opportunities presented to resume the promotion of his position. In search of allies, in 599 he included the Illyrian metropolitans, and later the emperor Phocas, in the circle of his addressees, and until the last years of his pontificate he wrote about the need to renounce the title to patriarch Cyriacus II of Constantinople. Summarizing, the author identifies and characterizes four stages of the dispute, and also, filling a gap in the available literature, examines the views of Pope Gregory on the semantic content of the title.